Visible Light Induced Degradation of Methylene Blue on Titanium Oxo Ethoxo Clusters of Type Ti16O16(OEt)32 - In, Su-Il; Berg, Regina (Asian Journal of Chemistry, 2011)
Titanium-oxo-ethoxo cluster, Ti16O16(OEt)32 (Ti16-cage) has been used as a nano-building block for advanced materials. Photocatalytic application may also be possible due to its molecular structure consisting of an inorganic titanium oxide core. However, the Ti16-cage is too unstable to examine its photocatalytic properties under atmospheric conditions. Herein it is shown for the first time that the aforementioned Ti16-cage is capable of/can be used for the degradation of organic dyes under visible light irradiation. A possible mechanism of this photocatalytic reaction is proposed.